Oxygen-doped sulfide electrolyte, preparation method and application thereof

By using mixed gas containing oxygen in a medium-free crusher for fine grinding and electrostatic removal operations, a gradient distribution structure of oxide cladding and internal oxygen element doping is formed, and the distribution of oxygen-doped sulfide electrolyte is solved. The problem of poor uniformity and stability has achieved the improvement of high ionic conductivity and air stability.

CN119275330APending Publication Date: 2025-01-07SUPERIONIC SOLID ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310797208.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing preparation methods for oxygen-doped sulfide electrolytes have problems such as uneven distribution of oxygen elements, decreased ionic conductivity, and poor stability, and it is difficult to achieve trace-level regulation and control of the doping amount of oxygen elements.

Method used

By fine grinding with mixed oxygen gases in a medium-free crusher, combined with electrostatic removal operations, a gradient distribution structure of oxide coating and internal oxygen element doping is formed to ensure uniform coating and low concentration doping of oxygen elements. It can improve the air stability and ionic conductivity of the electrolyte.

Benefits of technology

The high ionic conductivity and air stability of the sulfide electrolyte are achieved, the preparation process is simplified, batch synthesis is facilitated, and the integrity and stability of the oxygen cladding layer are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004322097410000171
    Figure BDA0004322097410000171
  • Figure HDA0004322097430000011
    Figure HDA0004322097430000011
  • Figure HDA0004322097430000012
    Figure HDA0004322097430000012
Patent Text Reader

Abstract

The invention discloses an oxygen element doped sulfide electrolyte, a preparation method and application thereof, the surface of the sulfide electrolyte contains a uniform oxide coating layer, and the interior of the sulfide electrolyte is doped with an oxygen element; the thickness of the oxide surface coating layer is 1-50nm, the oxygen element of the oxide-doped sulfide electrolyte is in gradient distribution, the structure can improve the air stability of the sulfide electrolyte, and the structure also can ensure that the oxygen coating shell is not easy to fall off because the doped oxygen element is less in amount and less in ionic conductivity loss, so that the performance of the sulfide electrolyte is improved. And the air stability of the sulfide electrolyte is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an oxygen-doped sulfide electrolyte, a preparation method and applications thereof. Background Art

[0002] In recent years, with the rapid popularization of electronic devices and electric vehicles, lithium-ion batteries, as a key power source device, have seen rapid development in related industries. With the improvement of the functions and performance of various devices, the market has put forward higher requirements for the high capacity, long cycle and safety of batteries. Currently, commercial lithium-ion batteries use liquid electrolytes for the conduction of lithium ions between the positive and negative electrodes. The problems of flammability, puncture and short circuit fire, and the large space occupied by liquid electrolytes in the battery still exist. Using inorganic solid electrolytes instead of liquid electrolytes can achieve higher battery energy density, simpler battery design and higher safety. Therefore, the design and synthesis of solid electrolytes are very important for the future development of batteries.

[0003] At present, inorganic solid electrolytes are mainly divided into two technical routes: oxide electrolytes and sulfide electrolytes. Among them, sulfide electrolytes are very suitable for all-solid-state batteries because they have ionic conductivity comparable to that of liquid electrolytes and a lower Young's modulus. However, the instability of sulfides to air and moisture will cause certain side reactions during the production process. The PS groups in the electrolyte react with moisture in the air to produce toxic H2S gas and cause a decrease in ionic conductivity. The doping of oxygen elements can inhibit side reactions in sulfide electrolytes and the generation of H2S gas, and oxygen-doped sulfide electrolytes can have better compatibility with commonly used oxide positive electrodes.

[0004] The current preparation methods of oxygen-doped sulfide electrolytes are divided into two types:

[0005] 1) Internal doping of oxygen elements. The oxygen elements are evenly distributed inside the electrolyte particles, and the preparation process is relatively cumbersome. For example, when oxygen elements are provided by doping raw materials containing oxygen elements (Li2O, P2O5, etc.), multiple ball milling is required to grind the raw materials during the raw material mixing process, and the raw materials that are hardened during grinding need to be manually broken, which takes a long time; in addition, the loss caused by the material sticking to the ball milling beads is also high.

[0006] When the above method is used, when the oxygen doping content inside the sulfide electrolyte particles is too high, the migration performance of lithium ions will deteriorate and the ionic conductivity of the electrolyte will decrease; and through this doping method, it is impossible to achieve uniform oxygen doping under the condition of a very low oxygen element ratio, and it is especially difficult to achieve uniform dispersion of the material during sintering.

[0007] There is a method that adds Li2O2, LiNO3 and other substances as oxidants to the raw materials and obtains oxygen-doped sulfide electrolytes after sintering. While the stability of the sulfide electrolytes obtained by this method is improved, other properties of the electrolyte, including ionic conductivity, are greatly reduced, and it is impossible to achieve trace-level regulation of the oxygen doping amount.

[0008] Another method is to dope oxygen by introducing a certain amount of oxygen into the sintering atmosphere during the sintering process. The sulfide electrolyte obtained by this method has an uneven distribution of oxygen, and the particles tend to deteriorate rapidly from the parts with less oxygen content, reducing the conductivity. In addition, the amount of oxygen doping is uncontrollable, and high temperature can easily cause the electrolyte to be over-oxidized, which greatly reduces the ionic conductivity.

[0009] 2) Although the surface is coated with an oxygen-containing layer, the proportion of oxygen doping can be reduced, but there is currently no mature preparation method, the coating efficiency is low, and it is difficult to control the thickness of the oxygen coating layer.

[0010] There is a method that controls the atmosphere in the ball mill, injects a certain amount of oxygen and argon mixed gas into it, and ball mills the sulfide electrolyte to obtain a sulfide electrolyte wrapped in an oxide layer. However, this method will cause the powder to be compacted and hardened during the ball milling process, and cannot form a complete oxide layer to cover the particles. The air stability is not good enough, and the different ratios of elements in the oxide shell and the inside of the particles cause discontinuity in physical properties, which makes the shell easy to fall off. In addition, ball milling will impose excessive mechanical stress on the electrolyte, destroy the crystal structure, and affect the ionic conductivity.

[0011] Another method is to expose the sulfide electrolyte to humid air so that the surface sulfide reacts with water vapor and oxygen to obtain a surface oxide layer, thereby obtaining an oxide-layer-coated electrolyte. However, the oxide layer formed by this method greatly affects the performance of the sulfide electrolyte, and the ionic conductivity is seriously reduced. In essence, the sulfide surface undergoes hydrolysis and oxidation, which is equivalent to a slow failure effect. The process of forming the shell, the thickness of the oxygen shell, and the amount of oxygen element doping are all uncontrollable. In addition, gases such as H2S are generated during the shell formation process, which are harmful to human health.

[0012] Therefore, there is an urgent need for more efficient and controllable methods to prepare oxygen-doped sulfide electrolytes. Summary of the invention

[0013] In response to the above technical problems, the present application provides an oxygen-doped sulfide electrolyte, a preparation method and an application thereof. The oxygen-doped sulfide electrolyte is a sulfide electrolyte obtained by de-milling and separating from the ball-milling medium, and the obtained sulfide electrolyte has a high ionic conductivity.

[0014] The specific technical solutions of this application are as follows:

[0015] The present application provides an oxygen-doped sulfide electrolyte, wherein the surface of the sulfide electrolyte contains a uniform oxide coating layer, and the interior of the sulfide electrolyte is doped with oxygen elements;

[0016] The thickness of the oxide surface coating layer is 1-50 nm.

[0017] Preferably, for the above-mentioned sulfide electrolyte, the thickness of the oxide coating layer is 5-15 nm.

[0018] Preferably, for any of the above-mentioned sulfide electrolytes, the overall doping amount of oxygen element is 0.01-1%, preferably 0.05-0.25%.

[0019] The present application provides a method for batch preparing oxygen-doped sulfide electrolytes, which comprises the following steps:

[0020] (1) mixing the raw materials uniformly and crushing them to obtain powder;

[0021] (2) finely grinding the powder to obtain finely ground powder;

[0022] (3) sintering the finely ground powder to obtain sulfide electrolyte powder;

[0023] (4) crushing the sulfide electrolyte powder to obtain crushed sulfide electrolyte powder;

[0024] (5) The crushed sulfide electrolyte powder is finely ground in a medium-free pulverizer using a mixed gas containing oxygen to obtain an oxide layer-coated sulfide electrolyte.

[0025] Preferably, in the above-mentioned method, the fine grinding in step (2) is to place the powder of step (1) into a medium-free pulverizer and finely grind the powder using a mixed gas containing oxygen to obtain a finely ground powder.

[0026] Preferably, for any of the above methods, the medium-free pulverizer is a jet mill or a thin film rotary mixer.

[0027] Preferably, for any of the above methods, in step (2), the oxygen is 0.01-5%, preferably 0.01-1%, by volume percentage in the mixed gas;

[0028] And / or in step (5), the oxygen is 0.1-5%, preferably 0.1-0.5%, by volume percentage in the mixed gas.

[0029] Preferably, for any of the above methods, in step (2) and / or (5), the pulverizing pressure for fine grinding is 0.1-1.0 MPa, preferably 0.2-0.7 MPa, and more preferably 0.2-0.4 MPa.

[0030] Preferably, in any of the above methods, a static electricity removal operation is performed in step (2) and / or in step (5), and preferably a static electricity removal operation is performed in both step (2) and step (5).

[0031] Preferably, in any of the above methods, the sulfide electrolyte is the sulfide electrolyte involved in any of the above methods.

[0032] The present application provides an all-solid-state battery, which comprises the sulfide electrolyte described in any one of the above items or the sulfide electrolyte prepared by any one of the methods described in any one of the above items.

[0033] Effects of the Invention

[0034] The oxygen element of the sulfide electrolyte prepared by the method described in the present application is distributed in a gradient. This structure can improve the air stability of the sulfide electrolyte and requires a smaller amount of oxygen doping, resulting in less loss of ionic conductivity. At the same time, this structure can also ensure that the oxygen-coated shell is not easy to fall off, further improving the air stability of the sulfide electrolyte. The process method of the present application is simple and fast, and is easy to achieve batch synthesis.

[0035] This application realizes surface coating of trace oxygen elements on particles in oxygen atmosphere collision by medium-free grinding under mixed gas containing oxygen, and combines with static electricity removal operation to make crushing more complete and oxygen doping more uniform. This method controls the crushing pressure and oxygen concentration of medium-free grinding to coat the raw material particles with oxygen elements more accurately, in trace amounts, and in a more uniform manner, and forms a sulfide electrolyte uniformly doped with trace oxygen elements inside after sintering. This trace and uniform oxygen doping is difficult to achieve in other methods.

[0036] This method can also coat the outer surface of the electrolyte particles doped with oxygen inside with a coating layer with a high oxygen content, forming a structure with low-concentration oxygen doping inside and oxygen shell coating outside. The overall oxygen concentration of the sulfide electrolyte is low, which minimizes the impact of oxygen on the electrolyte ion conductivity while achieving good air stability. The oxygen coating layer and the oxygen content inside the particles present a gradient oxygen concentration distribution, which is not easy to detach during sample preparation and reduce its air stability.

[0037] The method described in the present application realizes a pulverizing process of finer sulfide electrolyte and its raw material powder with lower hardness without agglomeration and adhesion by performing static electricity removal operation on raw materials and equipment during the use of a media-free pulverizer, thereby achieving better particle pulverization effect and uniform and controllable particle size and oxygen shell thickness of particles in a specified atmosphere.

[0038] Instruction Manual

[0039] Figure 1 This is an EDX schematic diagram of the oxygen-doped sulfide electrolyte prepared in Example 1.

[0040] Figure 2 Yes Figure 1 EDX schematic diagram magnified 24 times.

[0041] Figure 3 is perpendicular to Figure 1 EDX schematic diagram of the oxygen-doped sulfide electrolyte prepared in Example 1

[0042] Figure 4 Yes Figure 2 EDX schematic diagram magnified 24 times. DETAILED DESCRIPTION

[0043] The present application is described in detail below in conjunction with the described embodiments. Although specific embodiments of the present application are shown, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present application and to enable the scope of the present application to be fully communicated to those skilled in the art.

[0044] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the functional differences of components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" are open-ended terms and should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present application, but the description is based on the general principles of the specification and is not intended to limit the scope of the present application. The scope of protection of the present application shall be determined by the attached claims.

[0045] The present application provides an oxygen-doped sulfide electrolyte, the surface of the sulfide electrolyte contains a uniform oxide coating layer, and the interior of the sulfide electrolyte is doped with oxygen.

[0046] The oxygen-doped sulfide electrolyte refers to a sulfide electrolyte doped with oxygen. In the present application, the oxygen-doped sulfide electrolyte refers to a sulfide electrolyte having a uniform oxide coating layer on the surface and doped with oxygen inside the sulfide electrolyte.

[0047] A uniform oxide coating means that the oxygen element intensity is similar in all directions of the particles as measured by EDX oxygen element distribution testing, and the total intensity difference is within ±20%.

[0048] In the present application, the oxygen-doped sulfide electrolyte may have a crystal structure of a high- or medium-order crystal group (cubic, hexagonal, tetragonal, or trigonal system) or a glass-ceramic phase itself.

[0049] The thickness of the oxide surface coating layer is 1-50 nm, and preferably, the thickness of the oxide surface coating layer is 5-15 nm.

[0050] For example, the thickness of the surface uniform oxide coating layer can be 1nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, etc.

[0051] In some embodiments, the total doping amount of oxygen element is 0.01-1%, and further preferably 0.05-0.25%. In the present application, the total doping amount of oxygen element refers to the ratio of the signal intensity of O to the sum of the signal intensity of all elements in the EDX test.

[0052] For example, the overall doping amount of oxygen element can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.65%, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95%, 1%, etc.

[0053] In the present application, there is no limitation on the method for determining the thickness of the oxide coating layer, which can be tested by conventional methods in the art, such as XPS testing.

[0054] Specifically, the thickness of the oxide coating layer means: when the test depth of the XPS on the sample gradually deepens from 1nm to Xnm, if the peak area of ​​the 1s orbital of O measured by XPS at the X+1nm position in the test results differs by less than 5% from the peak area of ​​the 1s orbital of O measured by XPS at the Xnm position, then the thickness of the oxide coating layer is Xnm.

[0055] The overall doping amount of oxygen in the sulfide electrolyte refers to the ratio of the sum of the signal intensities of the oxygen element to the sum of the signal intensities of all elements at all scanning points in the electrolyte tested by EDX mapping, which is the overall doping amount of oxygen in percentage.

[0056] The determination method is to use a combination of STEM and element EDX mapping to test the O element signal intensity and compare it with the intensity of all element signals at each position.

[0057] In some embodiments, the sulfide electrolyte has the general formula (Li A )(G B )(S C )(X D ), where 0≤A≤12, 0≤B≤5, 0≤C≤12, 0≤D≤2,

[0058] G is selected from one or more of P, Si, Ge and Sn;

[0059] S is selected from one or more of S, O, N, Se and Te;

[0060] Z is selected from one or more of Cl, Br, I and F;

[0061] The oxygen-doped sulfide electrolyte described in the present application can improve the stability of the sulfide electrolyte and has higher ionic conductivity due to oxygen doping.

[0062] The present application also provides a method for preparing an oxygen-doped sulfide electrolyte, comprising the following steps:

[0063] (1) mixing the raw materials uniformly and crushing them to obtain powder;

[0064] (2) finely grinding the powder to obtain finely ground powder;

[0065] (3) sintering the finely ground powder to obtain sulfide electrolyte powder;

[0066] (4) crushing the sulfide electrolyte powder to obtain crushed sulfide electrolyte powder;

[0067] (5) The crushed sulfide electrolyte powder is finely ground in a medium-free pulverizer using a mixed gas containing oxygen to obtain an oxide layer-coated sulfide electrolyte.

[0068] In the present application, the present application does not impose any restrictions on the raw materials for preparing the sulfide electrolyte, which can be the raw materials commonly used in the art, for example, Li2S, P2S5, LiX, MX (X = Cl, F, Br, I, OH, O, O2, N, etc.; M = Ge, Si, Ta, La, Zr, Te, Se, Sn, Sb, etc.) can be used to prepare the sulfide electrolyte Li 7-a (M b P 1-b )SX a (0<a≤2, 0≤b≤1); Li2S, P2S5, GeS2, MS, LiX (X=Cl, F, Br, I, OH, O, O2, N; M=Ge, Si, Ta, La, Zr, Te, Se, Sn, Sb, etc.) can also be used to synthesize Li 10+c M 1+c P 2-c S 12 (-1≤c≤2); Li2S, P2S5, SiS2, MS, LiX (X=Cl, F, Br, I, OH, O, O2, N, etc.; M=Ge, Si, Ta, La, Zr, Te, Se, Sn, Sb, etc.) can also be used to synthesize Li 21-e Si3M d P 3-d S 23 X e (0≤d≤3, 0≤e≤3); X and M may be multiple, or M and X may not be included.

[0069] In the present application, there is no limitation on the equipment used for crushing, and the crushing can be carried out by conventional equipment in the art, such as an electric grinder, a dispersion tank, a rotary mill, a stirrer, a mixer, etc., but without using grinding media.

[0070] In some embodiments, fine grinding of the powder is to place the powder in a medium-free pulverizer and use a mixed gas containing oxygen to finely grind the powder to obtain finely ground powder. In some embodiments, crushing the sulfide electrolyte powder is to place the sulfide electrolyte powder in an electric grinder to crush it to obtain crushed sulfide electrolyte powder. In some embodiments, the medium-free pulverizer is a jet mill or a thin film gyratory mixer, preferably a jet mill.

[0071] The jet mill is a processing method that uses high-speed airflow to grind the surface of materials. It uses the high-speed rotating flow field generated by the airflow to make the materials rotate, collide and rub continuously in the airflow, thereby achieving the purpose of grinding. The jet mill has the advantages of high grinding efficiency, high grinding precision, and little damage to the material. It is widely used in fine grinding and ultrafine grinding of powder materials.

[0072] The thin film gyratory mixer utilizes the high-speed rotation of the container itself to form a super strong centrifugal force, so that the material impacts the inner wall to complete the crushing, and the material clings to the inner wall to form a state similar to a powder / liquid film during the mixing and crushing process. For example, the Japanese PRIMIX thin film high-speed mixer FILMIX model 56-L can be used.

[0073] In the present application, there is no limitation on the components other than oxygen in the mixed gas containing oxygen, and it may be, for example, dry argon, nitrogen, carbon dioxide, carbon monoxide, hydrogen, H2S gas, etc. or a mixed gas of several thereof.

[0074] In some embodiments, in step (2), the oxygen is 0.01-5%, preferably 0.01-1%, by volume percentage in the mixed gas; and / or

[0075] In step (5), the oxygen is present in an amount of 0.1-5%, preferably 0.1-0.5%, by volume percentage in the mixed gas.

[0076] For example, in step (2), the oxygen gas may be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, etc., in terms of volume percentage in the mixed gas;

[0077] In step (5), the oxygen can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, etc., in terms of volume percentage in the mixed gas.

[0078] In some embodiments, the particle size of the powder in step (1) and the sulfide electrolyte powder after crushing in step (4) are both 0.5-5 mm; and / or

[0079] The particle sizes of the powder after fine grinding in step (2) and the sulfide electrolyte powder after fine grinding in step (5) are both 0.1-40 μm.

[0080] For example, the particle size of the powder and the crushed sulfide electrolyte powder can be 0.5-5mm, 0.5-4.5mm, 0.5-4mm, 0.5-3.5mm, 0.5-3mm, 0.5-2.5mm, 0.5-2mm, 0.5-1.5mm, 0.5-1mm, 1-5mm, 1-4.5mm, 1-4mm, 1-3.5mm, 1-3mm, 1-2.5mm, 1-2mm, 1-1.5mm, 1.5-5mm, 1.5-4.5mm, 1.5-4mm, 1.5-3 .5mm, 1.5-3mm, 1.5-2.5mm, 1.5-2mm, 2-5mm, 2-4.5mm, 2-4mm, 2-3.5mm, 2-3mm, 2-2.5mm, 2.5-5mm, 2.5-4.5mm, 2.5-4m m, 2.5-3.5mm, 2.5-3mm, 3-5mm, 3-4.5mm, 3-4mm, 3-3.5mm, 3.5-5mm, 3.5-4.5mm, 3.5-4mm, 4-5mm, 4-4.5mm, 4.5-5mm, etc.;

[0081] The particle size of the finely ground powder and the finely ground sulfide electrolyte powder can be 0.1-40μm, 0.1-30μm, 0.1-20μm, 0.1-10μm, 0.1-5μm, 0.1-1μm, 0.1-0.5μm, 0.5-40μm, 0.5-30μm, 0.5-20μm, 0.5-10μm, 0.5-5μm, 0.5-1μm, 5-40μm, 5-30μm, 5-20μm, 5-10μm, 10-40μm, 10-30μm, 10-20μm, 20-40μm, 20-30μm, 30-40μm, etc.

[0082] In some embodiments, a static electricity removal operation is performed in step (2) and / or step (5), and preferably a static electricity removal operation is performed in both steps (2) and (5).

[0083] In the present application, there is no limitation on the method of removing static electricity, and conventional static electricity removal equipment may be used for removing static electricity.

[0084] The present application adopts a method of removing static electricity, which can make the collision of particles more complete, reduce agglomeration and adhesion to the wall of the vessel, and make the product more uniform.

[0085] In some embodiments, in step (2) and / or (5), the pulverizing pressure for fine grinding is 0.1-1.0 MPa, preferably 0.2-0.7 MPa, and more preferably 0.2-0.4 MPa.

[0086] For example, the pulverizing pressure for fine grinding can be 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, 1.0 MPa, etc.

[0087] In the present application, the feed pressure refers to the pressure of the equipment when the material enters the equipment in step (2) / or (5). The present application does not impose any restrictions on the feed pressure, which only needs to be greater than the crushing pressure. For example, the feed pressure can be 0.4-0.5Mpa.

[0088] In some embodiments, the sulfide electrolyte is the sulfide electrolyte described above.

[0089] In some embodiments, the method comprises the following steps:

[0090] (1) mixing the raw materials uniformly and crushing them to obtain powder;

[0091] (2) finely grinding the powder to obtain finely ground powder;

[0092] (3) sintering the finely ground powder to obtain sulfide electrolyte powder;

[0093] (4) crushing the sulfide electrolyte powder to obtain crushed sulfide electrolyte powder;

[0094] (5) The crushed sulfide electrolyte powder is finely ground in a medium-free pulverizer using a mixed gas containing oxygen to obtain an oxide layer-coated sulfide electrolyte. In some embodiments, the fine grinding in step (2) is to place the powder of step (1) into a medium-free pulverizer and finely grind the powder using a mixed gas containing oxygen to obtain a finely ground powder. In some embodiments, the medium-free pulverizer is a jet mill or a thin film gyratory mixer. In some embodiments, in step (2), the oxygen is 0.01-5%, preferably 0.01-1%, by volume percentage in the mixed gas; and / or in step (5), the oxygen is 0.1-5%, preferably 0.1-0.5%, by volume percentage in the mixed gas. In some embodiments, in steps (2) and / or (5), the pulverizing pressure for fine grinding is 0.1-1.0MPa, preferably 0.2-0.7Mpa, and more preferably 0.2-0.4Mpa.

[0095] In some embodiments, a static electricity removal operation is performed in step (2) and / or step (5), preferably a static electricity removal operation is performed in both step (2) and / or (5). In some embodiments, the sulfide electrolyte is the sulfide electrolyte described above.

[0096] The present application adopts the method described to prepare sulfide electrolyte. Since no grinding media is used in the preparation process, the crushing is caused by the mutual collision between particles. During the process, no excessive heat is generated to affect the properties of the crushed material. In addition, the medium-free crusher has a particle screening effect. The output particle size can be adjusted according to the difference between the feed pressure and the crushing pressure. The particles that reach the fineness will leave the crushing chamber and sink into the collector. The particle size distribution is concentrated, and excellent particle morphology and particle size consistency can be achieved, thereby ensuring product quality and controllability.

[0097] The sulfide electrolyte prepared by the method described in the present application has a gradient distribution structure of oxygen elements, which can improve the stability of the sulfide and reduce the loss of ionic conductivity.

[0098] The present application provides an all-solid-state battery, which comprises the sulfide electrolyte described above or the sulfide electrolyte prepared by the method described above.

[0099] The present application provides a general and / or specific description of the materials and test methods used in the experiments. In the following examples, unless otherwise specified, % means wt%, i.e., weight percentage. The reagents or instruments used without indicating the manufacturer are all conventional reagent products that can be obtained commercially.

[0100] 1. Test methods of this application

[0101] 1) Test method for electrolyte products: 120 mg of sulfide electrolyte is pressed into a tablet (370 MPa) in a mold, and the sample is subjected to an alternating current impedance test (EIS) using an electrochemical workstation. The test frequency range is 1 Hz to 5 MHz, and the ionic conductivity is calculated. After the sulfide electrolyte powder is placed in the air for 24 hours, the ionic conductivity of the electrolyte is tested again. The value is divided by the ionic conductivity before the exposure test to obtain the ionic conductivity retention rate of the sulfide electrolyte after the exposure test.

[0102] 2) Thickness of the oxide coating layer: Using XPS testing, the XPS test depth of the sample is gradually deepened from 1nm to Xnm. In the test results, the difference between the O1s peak area of ​​XPS measured at the X+1nm position and the O1s peak area of ​​XPS measured at the Xnm position is less than 5%, and the thickness of the oxide coating layer is Xnm. For example, the method for determining the thickness of the oxide coating layer adopts XPS testing, and tests are performed at different depths on the sample surface. When the O1s peak shape does not change significantly after a certain depth, this thickness is the thickness of the oxide coating layer. The average result of measuring three positions is the thickness of the oxygen-coated outer shell layer.

[0103] Specifically, the parameters of the XPS test method are as follows:

[0104] X-ray source: monochromatic AlKα ray (1486.6eV)

[0105] Determination spectrum: O1s

[0106] Sputtering conditions: C60+, 10.0kV

[0107] Sputtering speed: about 2nm / min.

[0108] (3 Overall doping amount of oxygen element in sulfide electrolyte: EDX mapping test is carried out using a transmission electron microscope; a straight line is taken at the edge of the electrolyte particle image, passing through the center point of the electrolyte particle image, and the starting point of the straight line is used as the starting point of the horizontal axis and the signal intensity is used as the vertical axis to draw a graph. The O element signal intensity of each point on the horizontal axis is added to obtain the total signal intensity of the O element, and the signal intensity of all elements at each point on the horizontal axis is added to obtain the total signal intensity of all elements. The ratio of the comprehensive signal intensity of the O element to the intensity of all signal elements is the overall doping ratio of the oxygen element; a straight line perpendicular to the above straight line and also passing through the center point of the electrolyte particle image is taken to obtain the total signal intensity of the O element on the straight line, and the above straight line is rotated 45° clockwise and counterclockwise from the center point of the electrolyte particle image to obtain two straight lines with an angle of 45° with the above straight line, and the total signal intensity of the O element on the two straight lines is obtained. If the total signal intensity of the O element on the above four straight lines differs within ±20%, it is considered that the oxygen coating layer is relatively uniform.

[0109] 2. Embodiment

[0110] Example 1 Preparation of sulfide electrolyte

[0111] (1) Li2S, P2S2 and LiCl were put into an electric grinder at a molar ratio of 2.5:0.5:1.0 (total mass of 1 kg) and ground at a speed of 60 rpm for 20 min to obtain powder.

[0112] (2) The powder is put into a jet mill with a feed pressure of 0.45 MPa and a crushing pressure of 0.40 MPa. The crushing gas source is 99.9% by volume argon and 0.1% by volume oxygen. Fine grinding is performed to obtain finely ground powder. D 90 The particle size is about 2 to 4 μm, and static electricity is removed during the fine grinding process.

[0113] (3) The finely ground powder was sintered in a vacuum atmosphere at a heating rate of 10°C / min, a sintering temperature of 550°C, and a holding time of 2h, and then cooled at room temperature to obtain a sulfide electrolyte powder.

[0114] (4) The sulfide electrolyte powder is crushed again in an electric grinder to obtain crushed sulfide electrolyte powder, wherein the grinding speed is 60 rpm and the grinding time is 30 min.

[0115] (5) The finely ground sulfide electrolyte powder is put into the air flow mill again, the feed pressure is 0.45MPa, the crushing pressure is 0.20MPa, and the crushing gas source is a mixed gas of 99.8% argon and 0.2% oxygen by volume. The static electricity is removed during the fine grinding process to obtain a sulfide electrolyte (Li6PS5Cl) doped with oxygen elements and having a uniform oxide coating layer on the surface. The sulfide electrolyte is measured by XPS, and the thickness of the oxide coating layer is measured to be 10nm. The total signal intensity of all elements such as O and Li, P, S, Cl, and O in the sulfide electrolyte is tested by EDX. The signal intensity distribution diagram is shown in the figure. Figure 1 As shown, the enlarged image magnified 24 times is as follows Figure 2 As shown, by comparison, the overall oxygen doping amount of the sulfide electrolyte is 0.15%.

[0116] from Figure 1 It can be seen that the EDX mapping test signal intensity of all elements in Example 1 is much greater than that of the O element, and the signal gradually increases from both sides to the middle, indicating that it is similar to a spherical particle. The sum of the element signal intensities at all points, the sum of the O signal intensities, and then the intensity ratio are calculated, and it can be obtained that the proportion of the O element to the total elements is 0.15%.

[0117] Figure 2 for Figure 1 From the enlarged image, it can be seen that the O element intensity is high on both sides, and the O element intensity is low and average in the middle, indicating that a shell-core structure with an O shell is formed; the O element signal intensity of the particles is symmetrical on the left and right, indicating that the oxygen shell of the particles is evenly coated.

[0118] and Figure 1 , 2 The element intensity distribution diagram on the straight line perpendicular to the direction is as follows Figure 3 , 4 As shown, Figure 3 The enlarged image magnified 24 times is as follows Figure 4 As shown, Figure 1 and Figure 3 The oxygen element strength difference is 5%, less than 20%, which proves that the oxygen element shell coating of the particles is relatively uniform.

[0119] Example 2 Preparation of sulfide electrolyte

[0120] The difference between Example 2 and Example 1 is that in step (2), oxygen with a volume content of 0.30% is introduced, and the volume of argon is 99.7%, and a sulfide electrolyte (Li6PS5Cl) is obtained. The thickness of the oxide coating layer measured in the same manner as in Example 1 is 10nm, and the overall doping amount of oxygen element is 0.22%. In step (2), the proportion of oxygen is increased, and more oxygen elements are doped inside. The stability is slightly improved compared with Example 1, but the ionic conductivity is significantly reduced. Among them, stability refers to the comparison of the ionic conductivity after exposure to air for 24 hours with the ionic conductivity before the exposure test. The relationship between the ionic conductivity of the oxygen-doped sulfide electrolyte obtained after preparation and the ionic conductivity of the electrolyte not doped with oxygen element is shown in Table 1.

[0121] Example 3 Preparation of sulfide electrolyte

[0122] The difference between Example 3 and Example 1 is that in step (2), 0.03% by volume of oxygen and 99.97% by volume of argon are introduced to obtain a sulfide electrolyte (Li6PS5Cl). The thickness of the oxide coating layer measured in the same manner as in Example 1 is 10 nm, and the overall doping amount of oxygen is 0.12%. In step (2), the proportion of oxygen is reduced, the internal doping of oxygen is less, the ionic conductivity is higher, but the stability is significantly lower than that of Example 1.

[0123] Example 4 Preparation of sulfide electrolyte

[0124] The difference between Example 4 and Example 1 is that in step (5), 0.10% by volume of oxygen and 99.9% by volume of argon are introduced to obtain a sulfide electrolyte (Li6PS5Cl), the thickness of the oxide coating layer measured in the same manner as in Example 1 is 5 nm, and the overall doping amount of oxygen element is 0.10%. In step (5), the proportion of oxygen is reduced, the oxygen coating layer is thinner, the ionic conductivity is higher, but the stability is significantly lower than that of Example 1.

[0125] Example 5 Preparation of sulfide electrolyte

[0126] The difference between Example 5 and Example 1 is that in step (5), 0.30% by volume of oxygen and 99.7% by volume of argon are introduced to obtain a sulfide electrolyte, which is doped with oxygen elements and has an oxide coating layer on the surface. The thickness of the oxide coating layer measured in the same manner as in Example 1 is 15 nm, and the overall doping amount of oxygen elements is 0.21%. In step (5), the proportion of oxygen is increased, the oxygen coating layer is thicker, and the stability is slightly improved compared with Example 1, but the ionic conductivity is significantly reduced.

[0127] Example 6 Preparation of sulfide electrolyte

[0128] The difference between Example 6 and Example 1 is that the crushing pressure in step (2) is 0.20 MPa, and the sulfide electrolyte (Li6PS5Cl) is obtained. The thickness of the oxide coating layer measured in the same manner as in Example 1 is 10 nm, and the overall oxygen doping amount is 0.11%. The reduction in crushing pressure in step (2) reduces the oxygen doping amount, the oxygen coating layer is thinner, the ionic conductivity is higher, but the stability is significantly lower than that of Example 1.

[0129] Example 7 Preparation of sulfide electrolyte

[0130] The difference between Example 7 and Example 1 is that the crushing pressure in step (5) is 0.40 MPa, and a sulfide electrolyte (Li6PS5Cl) is obtained. The thickness of the oxide coating layer measured in the same manner as in Example 1 is 15 nm, and the overall doping amount of oxygen element is 0.20%. The increase in crushing pressure in step (5) makes the oxygen coating layer thicker, and the stability is slightly improved compared with Example 1, but the ionic conductivity is significantly reduced.

[0131] Example 8 Preparation of sulfide electrolyte

[0132] The difference between Example 8 and Example 1 is that only the static electricity removal operation is performed in step (2) to obtain a sulfide electrolyte (Li6PS5Cl). The thickness of the oxide coating layer measured in the same manner as in Example 1 is 8 nm, and the overall oxygen doping amount is 0.14%. The static electricity removal operation in step (5) is eliminated, so that the oxygen coating in step (5) is insufficient, the coating layer becomes thinner, the ionic conductivity is higher, but the stability is significantly lower than that in Example 1.

[0133] Example 9 Preparation of sulfide electrolyte

[0134] The difference between Example 9 and Example 1 is that only the static electricity removal operation is performed in step (5) to obtain a sulfide electrolyte (Li6PS5Cl). The thickness of the oxide coating layer measured in the same manner as in Example 1 is 10 nm, and the oxygen doping amount is 0.13%. The static electricity removal operation in step (2) is eliminated, so that the oxygen doping in step (2) is insufficient, the oxygen doping amount is reduced, the ion conductivity is higher, but the stability is significantly reduced compared with Example 1.

[0135] Example 10 Preparation of sulfide electrolyte

[0136] The difference between Example 10 and Example 1 is that no static electricity removal operation is performed during the whole process, and a sulfide electrolyte (Li6PS5Cl) is obtained. The thickness of the oxide coating layer measured in the same manner as in Example 1 is 8 nm, and the overall oxygen doping amount is 0.09%. The static electricity removal operation of steps (2) and (5) is cancelled, so that the oxygen doping in step (2) is insufficient, the oxygen coating in step (5) is also insufficient, the oxygen doping amount is reduced, the ionic conductivity is higher, but the stability is significantly reduced compared with Example 1.

[0137] Example 11 Preparation of sulfide electrolyte

[0138] The difference between Example 11 and Example 1 is that different raw materials are used. Example 11 uses Li2S, P2S2 and GeS2 as raw materials in a molar ratio of 5:1:1 to prepare a sulfide electrolyte (Li 10 GeP2S 12 ), the thickness of the oxide coating layer measured by the same method as in Example 1 is 10 nm, and the overall doping amount of oxygen element is 0.16%. Examples 11-14 are synthesized using the patented method for different sulfide electrolytes, maintaining a high ionic conductivity while the air stability is not much different from that of Example 1, proving that other sulfide electrolytes can also be synthesized using this method.

[0139] Example 12 Preparation of sulfide electrolyte

[0140] The difference between Example 12 and Example 1 is that different raw materials are used. Example 12 uses raw materials of Li2S, P2S2, LiCl and SiS2 with a molar ratio of 9.5:1.5:1:3 to prepare the sulfide electrolyte (Li 20 Si3P3S 23 Cl), the thickness of the oxide coating layer measured by the same method as in Example 1 is 10 nm, and the overall doping amount of oxygen element is 0.15%.

[0141] Example 13 Preparation of sulfide electrolyte

[0142] The difference between Example 13 and Example 1 is that different raw materials are used. Example 13 uses Li2S and P2S2 as raw materials with a molar ratio of 1.5:0.5 to prepare a sulfide electrolyte (Li3PS4). The thickness of the oxide coating layer measured by the same method as Example 1 is 10 nm, and the overall oxygen doping amount is 0.14%.

[0143] Example 14 Preparation of sulfide electrolyte

[0144] The difference between Example 14 and Example 1 is that different raw materials are used. Example 14 uses Li2S and P2S2 as raw materials with a molar ratio of 3.5:1.5 to prepare the sulfide electrolyte (Li7P3S 11 ), the thickness of the oxide coating layer measured by the same method as in Example 1 is 10 nm, and the overall doping amount of oxygen element is 0.14%.

[0145] Comparative Example 1 Preparation of sulfide electrolyte

[0146] Comparative Example 1 is compared with Example 1, the difference between which is that step (2) uses ball milling to obtain a sulfide electrolyte (Li6PS5Cl), and the thickness of the oxide coating layer measured in the same manner as in Example 1 is 10 nm, and the overall oxygen doping amount is 0.28%. Using ball milling in step (2) will compact the material, which is likely to cause excessive and uneven oxygen doping, and the conductivity is low. Deterioration is likely to start from the part with less oxygen, and the stability is also poor.

[0147] Comparative Example 2 Preparation of sulfide electrolyte

[0148] Comparative Example 2 is compared with Example 1, the difference between which is that in step (5), ball milling is used to obtain the sulfide electrolyte (Li6PS5Cl), and the thickness of the oxide coating layer measured in the same manner as in Example 1 is 20 nm, and the overall oxygen doping amount is 0.22%. The use of ball milling in step (5) will compact the material and easily cause excessive oxygen coating, and the integrity and uniformity of the coating layer cannot be guaranteed. At the same time, the conductivity is low, and degradation is easy to start from the part with less oxygen, and the stability is also poor.

[0149] Comparative Example 3 Preparation of sulfide electrolyte

[0150] Comparative Example 3 is compared with Example 1. The difference is that in step (2), no oxygen is introduced but only argon is introduced to obtain the sulfide electrolyte (Li6PS5Cl). The thickness of the oxide coating layer measured in the same manner as in Example 1 is 10 nm, and the overall oxygen doping amount is 0.06%. In step (2), no oxygen doping is performed, and no oxygen element is contained inside. Although the ionic conductivity is relatively high, the stability is significantly lower than that of Example 1.

[0151] Comparative Example 4 Preparation of sulfide electrolyte

[0152] The difference between Comparative Example 4 and Example 1 is that in step (5), oxygen is not introduced to obtain the sulfide electrolyte (Li6PS5Cl), no oxide coating layer is contained, and the overall oxygen doping amount is 0.05%. In step (5), no oxygen coating is performed, no oxide coating layer is contained, and although the ionic conductivity is higher, the stability is significantly lower than that of Example 1.

[0153] Comparative Example 5 Preparation of sulfide electrolyte

[0154] The difference between Comparative Example 5 and Example 1 is that oxygen is not introduced in steps (2) and (5), and step (3) is modified as follows: the finely ground powder is sintered in a mixed gas of 0.1% oxygen and 99.9% argon, with a heating rate of 10°C / min, a sintering temperature of 550°C, a holding time of 2h, and cooling at room temperature to obtain a sulfide electrolyte powder. A sulfide electrolyte (Li6PS5Cl) is obtained, which does not contain an oxide coating layer, and the overall oxygen doping amount is 2.21%. The method is used for oxygen doping, and the results show that it is easy to overdo the oxygen doping at high temperature and the doping amount is difficult to control. Excessive oxygen doping makes its air stability relatively good, but the ionic conductivity is significantly reduced compared with Example 1, and it is difficult to use as a qualified electrolyte.

[0155] Comparative Example 6 Preparation of sulfide electrolyte

[0156] Comparative Example 6 is compared with Example 1, the difference being that in step (2), 5.0% by volume of oxygen and 95.0% by volume of argon are introduced to obtain a sulfide electrolyte (Li6PS5Cl), and no oxide coating layer is measured in the same manner as in Example 1, and the overall oxygen doping amount is 1.85%. In step (2), introducing excessive oxygen will result in an excessively high oxygen doping amount, and although the air stability is relatively good, the ionic conductivity is significantly lower than that of Example 1, and it is difficult to use as a qualified electrolyte.

[0157] Comparative Example 7 Preparation of sulfide electrolyte

[0158] Comparative Example 7 is compared with Example 1, the difference between which is that in step (5), 5.0% by volume of oxygen and 95.0% by volume of argon are introduced to obtain a sulfide electrolyte (Li6PS5Cl), and the thickness of the oxide coating layer measured in the same manner as in Example 1 is 40 nm, and the overall oxygen doping amount is 1.61%. In step (5), introducing excessive oxygen will result in an excessively high oxygen doping amount. Although the air stability is relatively good, the ionic conductivity is significantly lower than that of Example 1, and it is difficult to use as a qualified electrolyte.

[0159] Comparative Example 8 Preparation of sulfide electrolyte

[0160] Comparative Example 8 is compared with Example 1, and the difference is that in step (5), the electrolyte is placed in moist air with a humidity of 20% for 1 hour to obtain a sulfide electrolyte (Li6PS5Cl). The thickness of the oxide coating layer measured in the same manner as in Example 1 is 100 nm, and the overall oxygen doping amount is 5.36%. When oxygen is doped using this method, the oxidation decomposition of the electrolyte is accelerated by the presence of water, so that the coating layer is formed faster and thicker, and is difficult to control, and hydrogen sulfide gas is generated, resulting in the coating layer composition being different from that in the example, and the air stability is poor, while the ionic conductivity is significantly lower than that in Example 1, and it cannot be used as a qualified electrolyte at all.

[0161] Experimental Example Determination of ionic conductivity and calculation of ionic conductivity retention

[0162] The ionic conductivity of the sulfide electrolyte obtained in the examples and comparative examples was determined by the following specific determination method: 2 g of the sulfide electrolyte was weighed in a glove box and evenly sprinkled on a glass culture dish, and then the culture dish was placed in a reaction box with a specific humidity air flow, and allowed to stand at room temperature for 24 hours. The relative humidity of the dry air was 10%, and the air flow rate was 200 ml / min. After the standing, the sample was collected, the ionic conductivity was tested, and then it was exposed to the air for 24 hours, and the ionic conductivity of the sample was measured.

[0163] Calculate the retention rate of ionic conductivity using the following formula:

[0164] Ion conductivity retention rate = ion conductivity after exposure to air / ion conductivity in the reaction box, wherein the ion conductivity is measured as follows:

[0165] The electrolyte powder was filled into a cylindrical sleeve mold with a diameter of 1 mm and compacted under a pressure of 6 MPa. An electrochemical workstation was used to perform EIS test on the electrolyte sheet in the mold. A vernier caliper was used to test the sample thickness, and the ionic conductivity of the electrolyte was calculated.

[0166] The results are shown in Table 1.

[0167] Table 1 Ionic conductivity retention rate table

[0168]

[0169]

[0170] The electrolyte ion conductivity relationship refers to the ratio of the ion conductivity of the oxygen-doped sulfide electrolyte obtained after preparation to the ion conductivity of the electrolyte not doped with oxygen, that is:

[0171] A: ratio ≥98%;

[0172] B: 98%> ratio ≥ 95%;

[0173] C: 95%> ratio ≥ 90%;

[0174] D: 90%> ratio ≥ 10%;

[0175] E: ratio <10%.

[0176] It can be seen from Examples 1-10 that by adjusting the proportion of oxygen in the mixed gas in step (2) and / or step (5), selectively adding a static electricity removal step and adjusting the crushing pressure in step (2) and / or step (5), the oxygen doping and coating of the electrolyte can be optimized, thereby affecting the conductivity and the conductivity retention rate. In addition, the preferred proportion of oxygen in the mixed gas can further optimize the stability of the electrolyte.

[0177] It can be seen from Example 1 and Comparative Examples 1-2 in the above table that the ball milling method cannot achieve uniform and effective internal doping of oxygen elements, nor can it control the doping of relatively small amounts of oxygen elements to minimize the effect of affecting conductivity, and it is even more impossible to uniformly coat the oxygen elements on the surface of the particles to form perfect protection. Therefore, the air stability of the sulfide electrolyte prepared by the ball milling method is also poor.

[0178] It can be seen from Example 1 and Comparative Examples 3-4 that only internal doping with oxygen elements or only covering with oxygen shells will significantly reduce the air stability of the electrolyte.

[0179] In addition, the reason why the ionic conductivity of some comparative examples in Table 1 is high is that the electrolyte of the comparative example did not prepare the electrolyte of the structure of the present application, that is, some steps did not dope the oxygen element, resulting in its high conductivity, but the degradation was more serious after exposure to air.

[0180] While ensuring the conductivity retention rate of the electrolyte, Examples 1-14 also ensure a high ionic conductivity of the electrolyte, solving the problem that both air stability and ionic conductivity cannot be achieved in general oxygen doping or oxygen coating methods.

[0181] The above is only the preferred embodiment of the present application, and does not limit the present application in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present application without departing from the technical solution of the present application still falls within the protection scope of the technical solution of the present application.

Claims

1. An oxygen-doped sulfide electrolyte, wherein the surface of the sulfide electrolyte contains a uniform oxide coating layer, and the interior of the sulfide electrolyte is doped with oxygen; The thickness of the oxide surface coating layer is 1-50 nm.

2. The sulfide electrolyte according to claim 1, wherein The thickness of the oxide coating layer is 5-15 nm.

3. The sulfide electrolyte according to any one of claims 1 to 2, wherein The total doping amount of oxygen element is 0.01-1%, preferably 0.05-0.25%.

4. A method for batch preparation of oxygen-doped sulfide electrolytes, comprising the following steps: (1) mixing the raw materials uniformly and crushing them to obtain powder; (2) finely grinding the powder to obtain finely ground powder; (3) sintering the finely ground powder to obtain sulfide electrolyte powder; (4) crushing the sulfide electrolyte powder to obtain crushed sulfide electrolyte powder; (5) The crushed sulfide electrolyte powder is finely ground in a medium-free pulverizer using a mixed gas containing oxygen to obtain an oxide layer-coated sulfide electrolyte.

5. The method according to claim 4, wherein: The fine grinding in step (2) is to place the powder of step (1) into a medium-free pulverizer and grind the powder using a mixed gas containing oxygen to obtain a finely ground powder.

6. The method according to any one of claims 4 to 5, wherein: The medium-free pulverizer is a jet mill or a thin film rotary mixer.

7. The method according to any one of claims 4 to 6, wherein: In step (2), the oxygen is 0.01-5%, preferably 0.01-1%, by volume percentage in the mixed gas; And / or in step (5), the oxygen is 0.1-5%, preferably 0.1-0.5%, by volume percentage in the mixed gas.

8. The method according to any one of claims 4 to 7, wherein: In step (2) and / or (5), the pulverizing pressure for fine grinding is 0.1-1.0 MPa, preferably 0.2-0.7 MPa, and more preferably 0.2-0.4 MPa.

9. The method according to any one of claims 4 to 8, wherein: The static electricity removal operation is performed in step (2) and / or in step (5), and preferably the static electricity removal operation is performed in both step (2) and step (5).

10. The method according to any one of claims 4 to 9, wherein: The sulfide electrolyte is the sulfide electrolyte according to any one of claims 1 to 3.

11. An all-solid-state battery, comprising the sulfide electrolyte according to any one of claims 1 to 3 or the sulfide electrolyte prepared by the method according to any one of claims 4 to 10.

Citation Information

Cited By

  • Sulfide composite solid electrolyte, preparation method thereof, positive plate and solid-state battery

    CN122599516A